Digitalisasi Pemasaran dan Pencatatan Keuangan pada UMKM Obugame: (CV Eldanan Berkah Karya) - Rusti, Nanda; Kareja, Novilia; Febrita, Ruth Ema (Universitas Nusantara PGRI Kediri, 2023)
Financial recording and marketing are two challenges faced by business actors, especially micro, small and medium-scale enterprises (MSME). CVs also experience obstacles in these two areas. Eldanan Berkah Jaya. CV. Eldanan Berkah Karya is one of the MSMEs in Banyuwangi engaged in the food sector. This MSME grew from the concern of its owners, who saw the low price of agricultural products, especially when the harvest period came. Limitations in digital marketing and financial records encourage the service team to take part in efforts to support the growth and development of MSMEs. The service team created a website to digitize marketing and record finances in accordance with the business characteristics of Obugame. The Community Service Program (PKM) is expected to be able to develop a CV. Eldanan Berkah Jaya, especially in the field of financial management and development of marketing methods